IâJAZ AL-QURâAN IN THE VIEWS OF AL-ZAMAKHSYARI AND SAYYID QUTHB FUTUROLOGI PENDIDIKAN ISLAM - Asfiati, Asfiati (IAIN Padangsidimpuan, 2014)
Abstract: Islamic education never stops in arranging themselves towards change and development in accordance with the times. For that Islamic education find a new paradigm through reactive and defensive nature of the answer and defend the truth. In this case Islamic education should be able to make the concept and contains the basic values of the strategic and proactive and anticipatory, precedes the development of problems that will appear in the future, should also be able to defend the basic values true and is believed to be maintained and developed. Basic values embodied in the Quran and Sunnah and able to develop primordial testimony to the community and nation come about through education that serve as the media in educating the nations children. The values of sound policies will not be timeless and age so that they can be instrumental in achieving success though many Islamic educational futurology found social issues, politics, education and the impact of globalization and the discovery of the true identity of the nation.Keywords: Ijaz Quran, Sayyid Qutb, Futurology EducationÂ Abstrak: Pendidikan Islam tidak pernah berhenti dalam mengatur diri sendiri terhadap perubahan dan perkembangan sesuai dengan perkembangan zaman. Untuk itu pendidikan Islam menemukan paradigma baru melalui alam yang reaktif dan defensif dari jawaban dan membela kebenaran. Dalam hal ini pendidikan Islam harus mampu membuat konsep dan mengandung nilai-nilai dasar strategis dan proaktif dan antisipatif, mendahului perkembangan masalah yang akan muncul di masa depan, juga harus mampu mempertahankan nilai-nilai dasar yang benar dan diyakini dipertahankan dan dikembangkan. Nilai-nilai dasar yang terkandung dalam Al-Quran dan Sunnah dan mampu mengembangkan kesaksian primordial kepada masyarakat dan bangsa muncul melalui pendidikan yang berfungsi sebagai media dalam mendidik anak-anak bangsa. Nilai-nilai kebijakan yang baik tidak akan lekang oleh waktu dan usia sehingga mereka dapat berperan dalam mencapai kesuksesan meskipun banyak futurolog pendidikan Islam ditemukan masalah-masalah sosial, politik, pendidikan dan dampak globalisasi dan penemuan identitas bangsa.Kata kunci : Iâjaz Al-Qurâan, Sayyid Quthb, Futurologi Pendidikan